Analytical mechanics : an introduction - Fasano, A. (Antonio) (Oxford graduate texts., 2006)
Is the solar system stable? Is there a unifying 'economy' principle in mechanics? How can a pointmass be described as a 'wave'? This book offers students an understanding of the most relevant and far reaching results of the theory of Analytical Mechanics, including plenty of examples, exercises, and solved problems. - ;Analytical Mechanics is the investigation of motion with the rigorous tools of mathematics. Rooted in the works of Lagrange, Euler, Poincar--eacute--; (to mention just a few), it is a very classical subject with fascinating developments and still rich of open problems. It addres.